Part of Her: An Exploration of the Bodily Boundaries Between Parent and Child and the Limits of Personhood in Lina Meruane’s Sangre en el ojo - Sawnie Smith (Studies in 20th & 21st Century Literature, 2019)
Lina Meruane (1970-) is a contemporary Chilean author whose novels began to captivate at the turn of the twenty-first century. Her works are replete with unsettling meditations on the fragility of human flesh. And the promise of illness—its infectious potential—clings to the air in her literary worlds, such as those found in Fruta podrida (2007) and Sangre en el ojo (2012). This latter novel in particular serves as a vivid example of Meruane’s talent for writing sickly atmospheres. It is a novel saturated with bodily imagery, such as disembodied eyes, parasitic embraces, and grim sexual foreplay. All of these visuals are evoked by the protagonist of Sangre en el ojo, Lina, who is described as a Chilean academic and recently blinded type 1 diabetic, very much like the author herself. This essay uses Kay Torney Souter’s notion of the “family body,” articulated in her 1998 article, “Narrating the Body: Disease as an Interpersonal Event,” as a conceptual lens through which to contemplate these images. In short, the family body, as Souter articulates it, metaphorizes the biological. She argues that the onset of death and disease—all of these various degradations and mutations of the flesh—oblige one to confront the agonizing and ghostly business of participating in a genetic legacy. With this essay, I explore the various ways by which the disquieting bodily imagery of Lina Meruane’s novel is further enriched when contemplated using Souter’s notion. I argue that when contemplated through the prism of Souter’s notion, Meruane’s bodily imagery interrogates traditional notions of individuated (and healthy) personhood as achieved through fleshly circumscription.
Keywords: Lina Meruane; Kay Torney Souter; kinship; pathographies; conceptions of personhood; bodily boundaries; familial dynamics; illness; disease; blindness; division; adhesion